(untitled) (Contemporary Mathematics, 2025)
In this paper we define Wijsman λ-statistical convergence of order (α, β) and studied some properties of this concept. We also make an effort to define Wijsman λ-statistical convergence of Musielak-Orlicz function of order (α, β) and examine some topological properties.